Marginal Modernity : the Aesthetics of Dependency from Kierkegaard to Joyce. - Lisi, Leonard (Fordham University Press, 2012)
Two ways of understanding the aesthetic organization of literary works have come down to us from the late eighteenth century and dominate discussions of European modernism today: the aesthetics of autonomy, associated with the self-sufficient work of art, and the aesthetics of fragmentation, practiced by the avant-gardes. In this revisionary study, Leonardo Lisi argues that these models rest on assumptions about the nature of truth and existence that cannot be treated as exhaustive of modern experience.